Effect of C-terminus Conjugation via Different Conjugation Chemistries on In Vivo Activity of Albumin-Conjugated Recombinant GLP-1 - Junyong Park; Mijeong Bak; Kiyoon Min; Hyun-Woo Kim; Jeong-Haeng Cho; Giyoong Tae; Inchan Kwon (MDPI AG, 2021)
Glucagon-like peptide-1 (GLP-1) is a peptide hormone with tremendous therapeutic potential for treating type 2 diabetes mellitus. However, the short half-life of its native form is a significant drawback. We previously prolonged the plasma half-life of GLP-1 via site-specific conjugation of human serum albumin (HSA) at position 16 of recombinant GLP-1 using site-specific incorporation of p-azido-phenylalanine (AzF) and strain-promoted azide-alkyne cycloaddition (SPAAC). However, the resulting conjugate GLP1_8G16AzF-HSA showed only moderate in vivo glucose-lowering activity, probably due to perturbed interactions with GLP-1 receptor (GLP-1R) caused by the albumin-linker. To identify albumin-conjugated GLP-1 variants with enhanced in vivo glucose-lowering activity, we investigated the conjugation of HSA to a C-terminal region of GLP-1 to reduce steric hindrance by the albumin-linker using two different conjugation chemistries. GLP-1 variants GLP1_8G37AzF-HSA and GLP1_8G37C-HSA were prepared using SPAAC and Michael addition, respectively. GLP1_8G37C-HSA exhibited a higher glucose-lowering activity in vivo than GLP1_8G16AzF-HSA, while GLP1_8G37AzF-HSA did not. Another GLP-1 variant, GLP1_8A37C-HSA, had a glycine to alanine mutation at position 8 and albumin at its C-terminus and exhibited in vivo glucose-lowering activity comparable to that of GLP1_8G37C-HSA, despite a moderately shorter plasma half-life. These results showed that site-specific HSA conjugation to the C-terminus of GLP-1 via Michael addition could be used to generate GLP-1 variants with enhanced glucose-lowering activity and prolonged plasma half-life in vivo.